Taking a Fresh Look at Foreign Language Enjoyment Research in SLA: Current Status, Future Directions, and Pedagogical Implications - Guo, Yunxian; Qiu, Yexiang (Frontiers in Psychology, 2022)
Foreign Language Enjoyment (FLE), as the most prevalent positive emotion predicting L2 learners’ academic performance and well-being, and a critical factor contributing to the creation of positive micro-institutions, has received remarkable scholarly attention across the globe in the past eight years. Despite the fact that FLE is the most extensively investigated positive emotion and extant research has yielded abundant and invaluable findings, it is far from being adequately studied, leaving vast lacunas to be explored. Therefore, this conceptual review article is written to familiarize language education researchers, practitioners, instructors, and learners with the current status of FLE research and its potential applications in L2 education, and suggest potential avenues for future research. To this aim, by making a diachronical and synchronical delineation of extant literature with regard to the conceptualization and theorization of FLE, and the methodology of FLE research, we argue that it is incumbent on researchers to make a new line of enquiry into the actualization of the ascertained affordances of FLE and its transmission in the microsystem of the classroom. Subsequently, by drawing on the broaden-and-build theory and the control-value theory, we highlight the significance of conducting FLE research with theoretical triangulation and methodological diversity to validate data and minimum bias. Next, while highlighting the critical role of FLE in L2 education, we suggest some pedagogical implications with the hope of enlightening the practice of key stakeholders such as instructors, teacher educators, and teacher recruiters. In the end, the limitations of existing literature are explicated, and avenues for future studies on FLE in L2 education domain are put forward for interested researchers.